Feelings of Entrapment and Defeat Mediate the Association Between Self-Esteem and Depression Among Transgender Women Sex Workers in China - Chang, Ruijie; Wang, Huwen; She, Rui; Zhang, Shuxian; Tsamlag, Lhakpa; Shen, Qiuming; Shi, Yue; Wang, Zixin; Lau, Joseph T. F.; Wang, Ying; Cai, Yong (Frontiers in Psychology, 2019)
Background Transgender women sex workers have a high prevalence of depression. Low self-esteem and subsequent involuntary subordination (characterized by feelings of defeat and entrapment) are well-documented risk factors for depression. The object of the present study was to investigate the mediating effect of feelings of entrapment and defeat on the relationship between self-esteem and depression among transgender women sex workers in China. Methods A cross-sectional study was conducted in Shenyang and Guangzhou in 2017. Participants were 198 transgender women sex workers who completed a structured questionnaire assessing background characteristics, self-esteem, feelings of entrapment and defeat, and depression. Linear regression was used to test the mediation hypotheses. Results Of participants, 25.25% exhibited high levels of depression. Self-esteem scores were negatively correlated with depression scores (r = −0.54, p < 0.05, R2adj = 0.23), defeat scores (r = −1.68, p < 0.05, R2adj = 0.31), and entrapment scores (r = −1.67, p < 0.05, R2adj = 0.25). In the mediation hypothesis model, entrapment (r = 0.21, p < 0.05) and defeat (r = 0.08, p < 0.05) had a complete mediating effect on the relationship between self-esteem (Spearman’s r = −0.06, p = 0.36) and depression (R2adj = 0.61). Conclusions Feelings of entrapment and defeat mediated the association between self-esteem and depression. More focus is needed on monitoring feelings of defeat and entrapment among transgender women sex workers to mitigate the risk of depression.